The oestrid flies: biology, host-parasite relationships, impact and management - Colwell, D. D.; Colwell, D. D.; Hall, M. J. R.; Hall, M. J. R.; Scholl, P. J.; Scholl, P. J. (Wallingford :CABI Publishing, 2006)
This book provides a comprehensive discussion on current knowledge on the biology of oestrid flies. It includes 14 chapters, each dedicated to the discussion of the oestrid flies' systematics, morphology, host-parasite relationships, and life history. A detailed survey of each genus is described. Specific differences between the flies' adult and larval stages are emphasized. Such discussions will be of great significance to researchers in entomology, parasitology, biology and veterinary science.
Keywords: HH000 - Pathogen, Pest, Parasite and Weed Management (General); LL822 - Protozoan, Helminth, Mollusc and Arthropod Parasites of Animals, (New March 2000); VV220 - Protozoan, Helminth and Arthropod Parasites of Humans, (New March 2000); YY100 - Anatomy and Morphology (Wild Animals), (New March 2000); YY200 - Reproduction, Development and Life Cycle (Wild Animals), (New March 2000); ZZ380 - Taxonomy and Evolution